1980
DOI: 10.1139/y80-108
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of vasa deferentia from spontaneously hypertensive and normotensive Wistar rats

Abstract: Vasa deferentia from age-matched spontaneously hypertensive rats (SHR) compared with three strains of control rats were found to be hyperresponsive to low concentrations, 10 and 20 mM, of KCl (K+) but not to noradrenaline (NA); the SHR tissue also demonstrated a lower ED50 to K+. Significant differences in maximum tension between SHR and the control animals in response to K+ were not seen although maximum tension developed to K+ was always greater than that developed to NA in either SHR or a control group. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The diminished maximum response to NE by the iliac strips is in accord with similar findings with other tissues, most com monly, the aorta (4,6,8,30). The faster relaxation of the iliac strips following wash-out of NE agrees with similar responses of aortic strip in CFS (28,29), is consistent with the greater vasodilatory action of isoproterenol on the smaller vessels of SHR (7,19), but differs from the slower relaxation of aortic strips NPS (5,8,29).…”
Section: Discussionsupporting
confidence: 87%
“…The diminished maximum response to NE by the iliac strips is in accord with similar findings with other tissues, most com monly, the aorta (4,6,8,30). The faster relaxation of the iliac strips following wash-out of NE agrees with similar responses of aortic strip in CFS (28,29), is consistent with the greater vasodilatory action of isoproterenol on the smaller vessels of SHR (7,19), but differs from the slower relaxation of aortic strips NPS (5,8,29).…”
Section: Discussionsupporting
confidence: 87%
“…Recently, several reports have indicated that altered contractile function also occurs in nonvascular smooth muscle from SHR including stomach fundus [Altman et al, 1977] and vas deferens [Caulfieldet al, 1977;Yanagawa et al, 1978;Corbett et al, 1980], The findings of similar modifications of the contractile responses of these nonvascular smooth muscles to various stimulants that were previously described in vascular smooth muscles from SHR lend additional support to the contention that alteration in smooth muscle reactivity is not an adaptive change resulting from elevated blood pres sure. They go further and suggest that hyper tension in SHR may be associated with a gen eralized membrane defect in handling of Ca2+ by smooth muscle.…”
Section: Introductionmentioning
confidence: 60%
“…However, our present find ing of decreased alkaline phosphatase activ ity in vas deferens microsomal fractions from SHR is not in favor of this hypothesis. The commmon feature of decreased ATP-depen dent Ca2+ accumulation by both fundus and vas deferens microsomal fractions from SHR, on the other hand, may provide a cel lular basis for the previous reports on altered contractile function of muscle strips isolated from these two tissues in SHR [Altman et al, 1977;Caulfield et al, 1977;Yanagawa et al, 1978;Corbett et al, 1980]. Their collective findings of hyperreactivity toward norepi nephrine, K+ and Ba2+, increased Ca2+ de pendence of contraction in depolarized tis sue, enhanced relaxant effect of diazoxide and more rapid loss of contractile response to K+ in Ca2+-free medium strongly suggest that these altered contractile functions may be caused by faulty relaxation of these smooth muscles resulting from the alteration of Ca2+ handling properties.…”
Section: Discussionmentioning
confidence: 76%
“…Studies with non-vascular smooth muscle, where the haemodynamic influence is excluded, may help to identify primary changes of the smooth muscle cell membrane in hypertension. A few studies of this kind have been done using the genetically hypertensive rat and the stomach fundus and vas deferens were found to exhibit alterations similar to those previously described for vascular smooth muscle (Altman et al, 1977;Caulfield et al, 1977;Yanagawa et al, 1978;Corbett et al, 1980;Kwan et al, 1982). To gain further information on this problem we have made use of the interesting properties of the rat duodenum, which gives a biphasic response to some stimulants: low concentrations of K+ or bradykinin induce relaxation whereas higher concentrations of these agents also cause contraction (Antonio, 1968;Faber & van der Meer, 1973;Boschcov et al, 1984).…”
Section: Introductionmentioning
confidence: 64%